On distributive effects of optimal regulation for power grid expansion - Luis Ángel Herrera; Juan Rosellón (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
To date, the distributive implications of incentive regulation on electricity transmission networks have not been explicitly studied in the literature. More specifically, the parameters that a regulator might use to achieve distributive efficiency under price-cap regulation have not yet been identified. To discern these parameters is the motivation for the research presented in this paper. We study how different weight parameters affect the distributive characteristics of optimal price-cap incentive regulation for electricity transmission. We find that a regulator's use of ideal (Laspeyres) weights tends to be more beneficial for the Transco (consumers) than for consumers (the Transco).
Keywords: L50; L51; L94; Q40; Q42; 330; electricity transmission; incentive regulation; distributive efficiency